PENGARUH WHISTLEBLOWING SYSTEM DAN MORAL REASONING DALAM PENGUNGKAPAN FRAUD KEUANGAN DENGAN PEMAHAMAN AMAR MA’RUF NAHI MUNGKAR SEBAGAI VARIABEL MODERASI - Ruslan, Fatahillah; Wawo, Andi; Aditiya, Roby (ISAFIR: Islamic Accounting and Finance Review, 2022)
This research aims to determine the influence of whistleblowing system and moral reasoning on financial fraud disclosure with the understanding of amar ma'ruf nahi mungkar as a moderation variable which is then conducted a study at the Makassar City Inspectorate Office. This research is quantitative research with a descriptive research approach. The population in this study is the Makassar City Inspectorate Office. The sampling technique in this study is porposive sampling, while the sample in this study is the auditor staff with a working period as an auditor of at least one year, knows the ins and outs of the organization of the Makassar City Inspectorate Office, and knows the processes that occur within the Makasar City Inspectorate Office. The method of data collection is by using questionnaires that are shared directly. The data used in this study is primary data collected through questionnaire surveys. The results of this study show that whistleblowing systems cannot affect the disclosure of financial fraud, while moral reasoning can affect the disclosure of financial fraud. Then the understanding of amar ma'ruf nahi mungkar also cannot strengthen the influence of whistleblowing system and moral reasoning on the disclosure of financial fraud.